On the carrying capacity of the bone marrow survival niche in mice - Tonouchi, Keisuke; Yeh, Chen-Hao; Cain, Derek W.; Moseman, E. Ashley; Haynes, Barton F.; Wagh, Kshitij; Wiehe, Kevin; Kurosaki, Tomohiro; Kelsoe, Garnett (Frontiers in Immunology, 2025)
Plasmacytes, the effector arm of humoral immunity, produce sufficient amounts of specific antibodies to provide protection against infection or disease. The durability of this humoral protection depends on the generation of long-lived plasmacytes (LLPC), a specialized population that is capable of secreting antibody over long periods of times - years to decades. Here we investigate the role of constitutively active germinal centers (GCs) in generating the plasmacytes resident in bone marrow, a site critical for vaccine-induced LLPC to provide meaningful protection to infection and resistance to morbidity. In unimmunized B6.S1pr2-Cre mice, we show that a short period of conditional labeling marks 85% of gut-associated GC B cells and their progeny. Frequencies of labeled GC B cells fall over time, but frequencies of labeled bone marrow PC increase to approximately one-third of all bone marrow PC by 70-80 days after pulse labeling. Labeled, GC derived bone marrow PC express the identical isotypic distribution of the unlabeled PC in bone marrow. We conclude that the progeny of gut-associated GC B cells are responsible for most, and perhaps all, bone marrow PC and that under homeostatic conditions, serum antibody reflects exposure to gut antigens. Bone marrow occupancy by these gut-derived PC raises the possibility of competition with more transient, vaccine-induced humoral responses.